Fatores preditivos de dificuldade de exposição laríngea - Setton, Antonio Roberto Ferreira (2018)
Introduction: Despite the great technological evolution in medicine, given its anatomical location, the larynx still presents a great challenge to those who need to see it adequately for either diagnostic or therapeutic purposes. This difficulty increases when anatomical factors of some individuals are present. Objectives: To identify the existence of predictive factors of laryngeal exposure difficulty and to evaluate the association of these factors in conjunction with this difficulty of exposure. Method: A retrospective cross-sectional study was carried out based on a sample of 30 clinical and surgical records of individuals with laryngeal lesions treated surgically at the Otorhinolaryngology Service of a Philanthropic Hospital of the State of Sergipe in the years 2014 and 2015. We collected the registry of their measurements of cervical circumference, oral opening, thyroid distance, presence of micrognathia and laryngeal anterioration, modified Malampatti Index and the surgical technique used, if conventional (with straight tweezers and microscope) or variant (with angled tweezers and endoscopes), the latter used as a last resort for satisfactory laryngeal exposure during surgery. The data were statistically analyzed by means of simple and percentage frequencies when categorical variable, or mean and standard deviation when continuous variable. Fisher Exact test was used to evaluate the existing associations, and these were graphically represented by multiple correspondence analysis. The mean differences were tested by the Mann-Whitney test. Relative risks were adjusted to their respective confidence intervals through univariate Cox Regression and the software used was the R Core Team 2017. Results: The presence of micrognathia (P = 0,005) and predisposition were identified as predictive factors of difficult laryngeal exposure of the larynx (P = 0,005), both with a 9-fold greater risk of difficult laryngeal exposure, the cervical circumference above 40 cm (p = 0,041), with a 5-fold increased risk of difficult laryngeal exposure and the Mallampati III index IV (p = 0,009) with 10 times greater risk of laryngeal exposure. Conclusion: The Micrognathia, laryngeal anterioration, cervical circumference above 40 centimeters and modified Mallampati index III and IV, were identified as predictive factors of difficult laryngeal exposure with statistical significance. The association of these four predictive factors has a sensitivity of 100% and a specificity of 85% to predict difficulty in laryngeal exposure.